A platinum blue complex exerts its cytotoxic activity via DNA damage and induces apoptosis in cancer cells. (6th March 2017) - Adiguzel, Zelal; Ozalp‐Yaman, Seniz; Celik, Gokalp; Salem, Safia; Bagci‐Onder, Tugba; Senbabaoglu, Filiz; Cetin, Yüksel; Acilan, Ceyda
Abstract : Here, we describe the characteristics of a Pt‐blue complex [Pt4 (2‐atp)8 (H2 O)(OH)] (2‐atp: 2‐aminothiophenol) as a prodrug for its DNA‐binding properties and its use in cancer therapy. The nature of the interaction between the Pt‐blue complex and DNA was evaluated based on spectroscopic measurements, the electronic absorption spectra, thermal behavior, viscosity, fluorometric titration, and agarose gel electrophoresis. Our results suggested that the compound was able to partially intercalate DNA and appeared to induce both single‐ and double‐stranded breaks (DBS) on DNA in vitro, but no DSBs in cells. The ability of the compound to induce DNA damage was dependent on reactive oxygen species (ROS) in vitro. There was also elevated formation of ROS and SOD expression in response to drug treatment in cell culture. The complex was found to be more cytotoxic to cancer cells in comparison with noncancer controls using WST‐1 assay. The mean of cell death was determined to be apoptosis as assessed via biochemical, morphological, and molecular observations, including DNA condensation/fragmentation analysis, live cell imaging microscopy, TUNEL analyses, and increase in the levels of pro‐apoptotic genes such as Bag3, Bak, Bik, Bmf, and Hrk. Hence, the Pt‐blue complex under study grants premise for further studies. Abstract : A novel Pt‐blue complex induces DNA damage leading to apoptosis through oxidative stress and elevation of proapoptotic proteins in cancer cells.